Deciphering virus entry with fluorescently labeled viral particles - Hoffmann, Anja Barbara; Mazelier, Magalie; Léger, Psylvia; Lozach, Pierre-Yves (Influenza virus, 2018)
To infect host cells, viruses have to gain access to the intracellular compartment. The infection process starts with the attachment of viruses to the cell surface. Then a complex series of events, highly dynamic, tightly intricate, and often hard to investigate, follows. This includes virus displacement at the plasma membrane, binding to receptors, signaling, internalization, and release of the viral genome and material into the cytosol. In the past decades, the emergence of sensitive, accurate fluorescence-based technologies has opened new perspectives of investigations in the field. Visualization of single viral particles in fixed and living cells as well as quantification of each virus entry step has been made possible. Here we describe the procedure to fluorescently label viral particles. We also illustrate how to use this powerful tool to decipher the entry of viruses with the most recent fluorescence-based techniques such as high-speed confocal and total internal reflection microscopy, flow cytometry, and fluorimetry.
Gesehen am 06.03.2020